CROSS-CULTURAL UNDERSTANDING AS A TOOL FOR REDUCING CULTURAL MISUNDERSTANDINGS - Parera, Rosariani Felixia; Maharani; Fatresia, Susi; Sahib , Nurfaizah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
In a world that is becoming more connected, people from different cultures interact regularly in everyday life—whether in schools, at work, or through online communication. Such interactions frequently lead to cultural misunderstandings, which stem from differences in values, ways of communicating, and the mental frameworks people use to understand and interpret meaning. This article explores cross-cultural understanding as a strategic approach to reducing cultural misinterpretations, with an emphasis on identifying the reasons behind these misunderstandings, the teaching and communication methods that can help develop cross-cultural understanding, and the beneficial results that come from putting these strategies into practice. This study employs a qualitative method with a descriptive-analytical approach, combining theoretical viewpoints and research outcomes from eighteen academic sources published between 2021 and 2025.These sources are drawn from the fields of intercultural communication, applied linguistics, education, and social research methodology. The results show that cultural misunderstandings are mostly caused by ethnocentrism, problems in communication practices, differences in how people use metaphors and think, and a lack of proper intercultural skills among teachers and communicators. Strategies like training in intercultural communication skills, using games in teaching, adopting multicultural classroom methods, and incorporating technology in learning have been shown to effectively address these gaps. This article states that cross-cultural understanding helps decrease both how often and how serious miscommunication issues occur, and it also promotes inclusion, a sense of psychological safety, creativity, and long-term collaboration among people from different cultural backgrounds. Recommendations are offered to educators, policymakers, and future researchers who aim to enhance intercultural competence in a world that is becoming more diverse and globally connected.